Biomass and carbon of Guadua angustifolia and Bambusa oldhamii in two communities of the Northeastern Sierra of Puebla, México - Aguirre-Cadena, Juan Francisco; Ramírez-Valverde, Benito; Cadena-Iñiguez, Jorge; Juárez-Sánchez, José Pedro; Caso-Barrera, Laura; Martínez-Carrera, Daniel (Revista de Biología Tropical, 2018)
The increase of CO2 in the atmosphere can be reduced by capturing them through the photosynthetic process, with special emphasis on fast growing perennial species such as bamboo. The objective of the present study was to quantitatively evaluate the aerial biomass and estimate the carbon content for the species Guadua angustifolia Kunth and Bambusa oldhamii Munro, in commercial plantations established in communities of the Northeast Sierra of Puebla, Mexico. The estimation of population and aerial biomass for both species is tended by a selection of 10 % of plants in one hectare. The samplings were carried out from June 2016 to September 2017. For the plantation of B. Oldhamii Munro, the number of culms per plant gradually increased towards the most recent generations, from 3.6 stems in the most adult cohort to 4.5 in the youngest. The diameter of the stems and their average height show a gradual increase from the older cohorts to the recent cohorts. The total aerial biomass estimated in the plantation of B. oldhamii Munro was 103 403 48 Mgha-1 distributed in the asses of the four years. The total aerial biomass estimated in the plantation of G. angustifolia Kunth is 47 665 11 Mgha-1.